Self-Regulated Learning in Writing of EFL Learners - Ariyanti, Ariyanti; Fitriana, Rinda; Pane, Widi Syahtia (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
This research was aimed to investigate EFL students’ Self-Regulated Learning in writing. Self-Regulated Learning itself means the method that students take control in understanding of knowledge from the lecturer by conducting their own way in learning. The design of this study was quantitative with survey design to measure students’ academic self-regulation and self-regulation in writing class context. The population of this study were third semester students of English Department of University of Widya Gama Mahakam Samarinda, Indonesia, which consist of two classes with totally 37 students, who have studied English writing. Questionnaire were applied to measured two aspects; students’ academic self-regulation (77 items) and self-regulation concerning English writing subject (14 items), using Likert Scales. The result showed that 70% of students were able to motivate themselves to learn writing, do some efforts to engage the class, willingly to rehearse, elaborate and organize the lesson material by themselves, meanwhile 19% students have better self-regulation that make them conducted better effort to learn writing and accomplished better as well and 11% of them still struggle to survive in writing class. It proved by the mean of three indicator; Learning Activeness (3.18), Willingness to respond lecturer's suggestion (3.12), and Willingness to broaden writing skill (3.27). To sum up, it can be considered that students had good enough self-regulation in writing.